2018
DOI: 10.1016/j.bcp.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation of arylamine N-acetyltransferase 1 by adenosine triphosphate

Abstract: In the present study, a screen of adenosine analogs as potential modulators of arylamine-Nacetyltransferase 1 activity identified ATP as an inhibitor within its range of physiological concentrations. Kinetically, ATP was a non-competitive inhibitor with respect to the acetyl acceptor but a competitive inhibitor with respect to the acetyl donor (acetyl-coenzyme A). In silico modelling predicted that ATP bound within the active site cleft arranged with the triphosphate group in close proximity to arginine 127. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The positions of p300 and NAT1 are shown. p300/CBP and SIRT1/2 Regulate NAT1 Acetylation (Minchin et al, 2018). In cells transfected with NAT1 alone, ATP (1 mM) decreased enzymatic activity in cytosolic preparations by 40% from 35 6 3 to 21 6 0.5 nmol/min per density unit (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The positions of p300 and NAT1 are shown. p300/CBP and SIRT1/2 Regulate NAT1 Acetylation (Minchin et al, 2018). In cells transfected with NAT1 alone, ATP (1 mM) decreased enzymatic activity in cytosolic preparations by 40% from 35 6 3 to 21 6 0.5 nmol/min per density unit (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Recent studies have suggested that NAT1 protein modifications regulate enzyme function. For example, alterations to lysine 100 (K 100 ) by site-directed mutagenesis decreased the affinity of the acetyl donor acetyl coenzyme A (AcCoA) for the protein (Minchin et al, 2018), suggesting it was important for AcCoA binding in the active site (Minchin and Butcher, 2015). K 100 has also been associated with ATP binding to NAT1 (Minchin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both orthologues are controlled by a conserved Sp1-type housekeeping promoter, adjacent to an upstream non-coding exon 1113 , and are potentially subject to epigenetic regulation 14,15 . Human NAT1 is also controlled by a second, more tissue-specific promoter 16 , and regulation has been shown to implicate steroid hormones 1720 , micro-RNAs 21,22 , protein polyubiquitinylation 23,24 , as well as acetylation of the enzyme and allosteric modulation by adenosine triphosphate 25,26 . Human NAT1 and rodent NAT2 proteins have been demonstrated to acetylate the same arylamine substrates 27 , including p-aminobenzoylglutamate (pABGlu), a catabolic derivative of folate 4,2730 .…”
Section: Introductionmentioning
confidence: 99%